EFFICACY AND SAFETY OF ANGIOTENSIN RECEPTOR BLOCKERS IN STAGE 1 HYPERTENSION: A HOSPITAL-BASED OBSERVATIONAL STUDY - JAINISH KAMLESHKUMAR MODI; MADHU YADAV (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study aimed to evaluate the efficacy, safety, and tolerability of three commonly used angiotensin receptor blockers (ARBs)-losartan, telmisartan, and olmesartan-in managing stage 1 hypertension among patients aged 40–60 years. Methods: A prospective observational study was conducted at a tertiary care hospital from March 2023 to March 2024. A total of 100 patients with stage 1 hypertension, as per joint national committee 8 criteria, were enrolled. Patients were randomly assigned to receive losartan (50–100 mg), telmisartan (40–80 mg), or olmesartan (20–40 mg) as monotherapy. Blood pressure, biochemical parameters, and adverse effects were monitored at baseline and at 15-day intervals for 3 months. Patients with secondary hypertension or compelling indications for other antihypertensive classes were excluded from the study. Results: All three ARBs effectively reduced systolic and diastolic blood pressure (DBP). At 3 months, Olmesartan showed the highest mean reduction (systolic blood pressure: 30 mmHg, diastolic blood pressure: 16 mmHg), followed by telmisartan (26/12 mmHg) and losartan (20/12 mmHg). There were no significant changes in lipid profiles, renal function, or serum electrolytes. Only one patient experienced a mild headache with olmesartan. No serious adverse events occurred, and compliance was 100% throughout the study period. Conclusion: ARBs are effective and well-tolerated in the treatment of stage 1 hypertension. Olmesartan demonstrated superior blood pressure control compared to losartan and telmisartan, without significant impact on biochemical parameters, highlighting its potential as a preferred monotherapy option.